THREE CASES OF BENIGN DISEASE PRESENTING MAXILLARY BONE DESTRUCTION SUSPECTING INFLAMMATORY PSEUDOTUMOR - Tukuda, Mamoru; Seki, Akihiko; Motimatsu, Izumi; Kagata, Hiroko; Kawai, Satoshi (JIBI INKOKA TEMBO, 1998)
Three cases of benign disease presenting maxillary bone destruction are reported. In all cases we performed biopsy of the maxillary sinus by exploratory antrotomy for the purpose of definitive diagnosis. Pathological findings showed proliferating plasma cells and lymphocytes, and diffuse fibrosis. In these proliferating cells, atypia could not be seen. In all cases pathological diagnosis was non-specific inflammation. When a clinically malignant disease is suspected but pathologically no malignancy is found, the disease is generally called inflammatory pseudotumor. It is considered that these three cases can be called inflammatory pseudotumor in a wide sense. Mycosis is one which requires differential diagnosis. Because PAS and Grocott staining of these specimens tested negative, mycosis was excluded. In all cases maxillary radical operation was performed, and there has been no recurrence until now.